Effect of belowground herbivory on parasitoid associative learning of plant odours. Issue 7 (13th December 2012) - Kruidhof, H. Marjolein; de Rijk, Marjolein; Hoffmann, Daniela; Harvey, Jeffrey A.; Vet, Louise E. M.; Soler, Roxina
<x xml:space="preserve">Abstract</x> Root herbivores can influence both the performance and the behaviour of parasitoids of aboveground insect herbivores through changes in aboveground plant quality and in the composition of the plant's odour blend. Here we show that root herbivory by Delia radicum larvae did not influence the innate preferences for plant odours of the two closely related parasitoid species Cotesia glomerata and C. rubecula, but did affect their learned preferences, and did so in an opposite direction. While C. glomerata learned to prefer the odour of plants with intact roots, C. rubecula learned to prefer the odour of root‐infested plants. The learned preference of C. glomerata for the odour of plants with intact roots matches our previously published result of its better performance when developing in P. brassicae hosts feeding on this plant type. In contrast, the relatively stronger learned preference of C. rubecula for the odour of root‐infested plants cannot be merely explained by its performance, as the results of our present study indicate that D. radicum root herbivory did not influence the performance of C. rubecula nor of its host P. rapae. Our results stress the importance of assessing the influence of root herbivores on both innate and learned responses of parasitoids to plant odours.